Static structural analysis of two-wheeler rim with different spoke patterns and materials - Srihari, G.; Saikiran, P.; Prasad, K. Durga; Goud, R. Raman; Srikanth, M.; Vemanaboina, Harinadh (AIP conference proceedings, 2023)
A wheel is a circular frame of hard material that is intended to rotate on an axle bearing. The alloy wheels have always been a subject of interest among high performance bikers. A lot of research work has been going on the different alloy materials and design for the wheels. Now a days most of the bikes coming with high engine power. So the wheel rim need to withstand high speed and forces caused by path holes and sudden braking. The main objective of our project is to design spoke patterns that focus on reducing the stresses, total deformation in the wheel. In this project we are designed different types of spoke patterns using CATIA V5 software and finding the best suitable spoke pattern. The design model can be analyzed under static structural conditions using Ansys workbench software. We analyzed the designed wheel pattern by modifying the spoke pattern, radius at the intersection of the spoke and hub in the design. By analyzing the design model on Ansys workbench using carbon steel 1008, aluminum 356 and carbon fiber materials we found maximum stress, total deflection and equivalent strain in the wheel rim under static structural conditions. The boundary conditions that we applied on the wheel are pressure on the circumference on the wheel rim, force at the center of the wheel and fixed support at the wheel hub. In this paper we had compared the different spoke patterns under static conditions. We are also comparing the spoke patterns under three different materials (carbon steel 1008, aluminum 356, carbon fiber). We can conclude best wheel pattern and best suitable material used for wheel rim.